Review of the botanical, chemical, pharmacological and toxicological aspects of Tridax procumbens L. (Research, Society and Development, 2022)
Medicinal plants, historically, are used by man in the prevention and cure of diseases. Due to their therapeutic properties, they are important instruments for pharmaceutical care and their valuation is guided by the World Health Organization. For example, Tridax procumbens L, belonging to the Asteraceae family, popularly known as erva-de-touro, has leaves and flowers with therapeutic activities. Therefore, the present study aimed to carry out a narrative review of the botanical, chemical, pharmacological and toxicological aspects of T. procumbens. In this way, a variety of chemical constituents of the studied species can be identified, encompassing the presence of saturated and unsaturated fatty acids, alkaloids, carbohydrates, polyphenols and tannins. These are possibly related to pharmacological and biological activities, where it was possible to verify the antimicrobial, anticoagulant, anticancer and anti-inflammatory and larvicidal activities. In relation to toxicological tests, they showed that T. procumbens did not show toxicity, even at high concentrations, showing a high margin of safety. Thus, this set of information demonstrates the importance of this species. However, further studies on chemical compounds, pharmacological and biological activities of Organs vegetative and reproductive organs of the species are necessary since they may have the potential to encourage incorporation in future studies.